1994
DOI: 10.1007/bf00114166
|View full text |Cite
|
Sign up to set email alerts
|

Comparative reproduction and nonparasitic development of Boophilus microplus and hybridized Boophilus ticks (Acari: Ixodidae) under natural field conditions in subtropical South Texas

Abstract: The reproductive biology and nonparasitic development of Boophilus microplus (Canestrini) and hybridized Boophilus ticks (B. annulatus (Say) male x B. microplus female) held under natural field conditions in south Texas throughout the year were compared. Comparisons between the two types of ticks indicated that the ovipositional biology (percentage of ovipositing females and number of eggs laid) of the females favored hybrid ticks during some months and B. microplus ticks during other months. However, on a yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 24 publications
(22 reference statements)
1
15
0
1
Order By: Relevance
“…Climatic conditions would favor the development of adult ticks during autumn and winter (DAVEY et al, 1980a, b;DAVEY;COOKSEY;DESPINS, 1991;DAVEY, 1988;BARRIGA;DA SILVA;AZEVEDO, 1995). Davey, Pound and Cooskey (1994) found more eggs laid in spring and autumn and the egg hatchability were essentially equal during the study. Furthermore, when the relative humidity (RH) is equal or above 75%, temperature becomes the main factor that determines larvae survival; in contrast, when RH is equal or less than 63%, it becomes the main factor substituting temperature (DAVEY; COOKSEY; DESPINS, 1991).…”
Section: Discussionmentioning
confidence: 61%
“…Climatic conditions would favor the development of adult ticks during autumn and winter (DAVEY et al, 1980a, b;DAVEY;COOKSEY;DESPINS, 1991;DAVEY, 1988;BARRIGA;DA SILVA;AZEVEDO, 1995). Davey, Pound and Cooskey (1994) found more eggs laid in spring and autumn and the egg hatchability were essentially equal during the study. Furthermore, when the relative humidity (RH) is equal or above 75%, temperature becomes the main factor that determines larvae survival; in contrast, when RH is equal or less than 63%, it becomes the main factor substituting temperature (DAVEY; COOKSEY; DESPINS, 1991).…”
Section: Discussionmentioning
confidence: 61%
“…This is in agreement with Teel et al (1996), who characterized South Texas habitats of canopied mesquite and mixed-brush vegetation as more favorable for higher numbers and longer survival of cattle ticks than grass and grass-mixed brush. Davey et al (1994) also found whether or not an area was favorable to R. microplus larvae survival was determined by temperature and humidity requirements, and these varied by season. In their study, they separated bufflegrass, Cenchurus ciliarus L., with no overstory (grass habitat) from bufflegrass with a mesquite, Prosopis glandulosa Torrey, overstory (shade habitat).…”
Section: Discussionmentioning
confidence: 99%
“…The type of vegetation affects the microenvironment, making a site favorable or unfavorable for larval survival (Fleetwood and Teel 1983;Sutherst 1983;Teel 1984;Garris and Popham 1990). Teel et al (1997) and Davey et al (1994) characterized South Texas habitats of canopied mesquite and mixedbrush vegetation as more favorable for higher numbers and longer survival of cattle fever ticks than grass and grass-mixed brush. The dynamics of tick infestation and occurrence is a complex function of many factors, which may include the degree of contact between cattle and white-tailed deer, climatic variables, and geographic locations to habitat and water.…”
Section: Introductionmentioning
confidence: 99%
“…Temperatures recorded in September through mid November and mid February through May were similar. Temperatures recorded during this study compared favorably with historical records for the region (National Oceanic and Atmospheric Administration 1983), as well as those recorded during a previous 2-year study conducted at the same site (Davey et al 1994).…”
Section: Resultsmentioning
confidence: 88%